(NlEO[ qNA^EK I RUSSKAQ KULXTURA(B.s (NMONOGRAFIQs - (Na(B.(NgOZENPUDs ((NlELINGRADs (NKOMPOZITORs, 1984)
(NgLUBOKI I PLODOTWORNY SWQZI RUSSKOJ I ^E[SKOJ MUZYKALXNYH KULXTUR(B.s
Keywords: (NmONOGRAFIQs